MENINGKATKAN KARAKTER ANAK MELALUI PENDEKATAN SAINTIFIK DI RA AL IKHLAS KABUPATEN BARRU - Andi Rezky Nurhidayah; Riskal Fitri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2019)
Abstract: Improving Children Character through Scientific Approach in RA Al Ikhlas Barru Regency. This research aimed to describe and improve children character through scientific approach in RA Al Ikhlas Barru Regency. This research used class action research (CAR). The subjects of research were RA Al Ikhlas students with 22 students consisted of 8 men and 14 women in the 2019/2020 school academic year. The instruments were observation sheet, interviews, and documentation. The data were analyzed using quantitative and qualitative data analysis techniques. The success indicators of action in this research were seen from the overall activity of children in each cycle had increased and showed the level of children character in RA Al Ikhlas Barru Regency overall reached the mastery of 85% with the value of each research subject obtained the lowest score of 61. Based on the results of classroom action research after implementing the scientific approach, information was obtained that in the first cycle students had complete character only 13 students or 59.1% and in the second cycle increased to 20 students or 85%. Therefore, it was concluded that the scientific approach could improve the students’ character of RA Al Ikhlas Barru Regency.